Hydrocarbon evolution of the Bredasdorp Basin, offshore South Africa : from source to reservoir - Davies, Christopher Paul Norman; Rozendaal, A.; Burger, B. V. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Geology))--University of Stellenbosch, 1997.